Worry and Discrimination of Threat and Safety Cues: An Event-Related Potential Investigation. Issue 5 (September 2015) - Grant, DeMond M.; Judah, Matt R.; White, Evan J.; Mills, Adam C.
Abstract Overgeneralization of fear to safety cues is increasingly being studied in order to further our understanding of the maintenance of anxiety disorders. The current study used event-related potentials (ERPs) to evaluate whether worry affects anticipation and processing of threat and neutral pictures during a conditioning task. Fifty-two high (n = 24) and low (n = 28) worriers completed a paradigm in which a neutral stimulus indicated the valence of a second stimulus, either a threat or neutral picture. Results found that worriers displayed reduced anticipatory responses to both stimulus types as indexed by the stimulus preceding negativity, although they displayed an increased stimulus preceding negativity to threatening images during the second half of the task. In addition, high and low worriers differed in processing of threat and neutral images as indexed by the late positive potential. These findings support the overgeneralization of fear literature, suggesting that worriers display difficulty discriminating safety cues from threat cues, and this affects the attentional resources devoted to subsequent stimuli. Implications of these results are discussed.